Knowledge and attitude towards human milk banking among undergraduate medical students - Yadav, N (Devdaha Medical Journal, 2025)
Introduction: Human milk banks provide screened and processed donor milk to preterm infants, those who have a low birth weight, or lack access to their mother’s milk due to maternal illness, disability, admission to an ICU, or insufficient milk production. This study aimed to assess the knowledge and attitudes of undergraduate medical students towards human milk banking. Methods: A cross-sectional study was conducted among undergraduate medical students studying at the College of Medical Sciences-Teaching Hospital in Bharatpur, Chitwan, Nepal. A total of 159 students participated, comprising 86 males and 73 females. The study included first-and second-year students pursuing a Bachelor of Medicine and Bachelor of Surgery (MBSS) degree. Data were collected using a structured questionnaire and analyzed using Microsoft Excel. Results: The mean age of participants was 20.48 ± 1.51 years. Of the total participants, 54.1% were male and 45.9% females. The majority of participants were Hindu (93.7%), followed by Muslim (3.1%), Christian (1.9%), and Buddhist (1.3%). The majority of participants (64.2%) had heard of human milk banking. The primary sources of information were social media, followed by health professionals, family and friends, and newspapers, which were the least common source. In this study, 47.8% of undergraduate medical students had adequate knowledge about human milk banking, 40.3% had moderately adequate knowledge, and 11.9% had inadequate knowledge. Similarly, 47.8% of students had a neutral attitude, 40.9% had a favorable attitude, and 11.3% had an unfavorable attitude about human milk banking. Conclusion: The findings indicate that undergraduate medical students, overall, possessed adequate knowledge and a favorable attitude toward human milk banking.